Gelling qualities of water soluble carbohydrate from Agave americana L. leaf extracts. (June 2020) - Bouaziz, Mohamed Ali; Mokni, Abir; Masmoudi, Manel; Bchir, Brahim; Attia, Hamadi; Besbes, Souhail
Abstract: The chemical composition of Agave americana leaves and their water soluble carbohydrate extract (WSCE) were determined. The hydrocolloid extract yield based on dry material was 55% (w/w). The contents of ash, lipid, crude protein, total sugars and total dietary fiber were 1.2, 4.7, 23, 40 and 42.6%, respectively. The WSCE showed the highest level of soluble sugars and a lower level of soluble fiber compared to the agave leaves (66 versus 18.3 and 7 versus 9.3%, respectively). The texture of pectin and WSCE:pectin mixed gels was also investigated. WSCE showed positive effects such as increased gel firmness. For the mixed gels, the maximum synergy was observed at 4% pectin concentration. Higher firmness, elasticity and a good general appearance of the mixed gels were observed compared to those of control gel (gel with only pectin at 4%). These results showed the beneficial interaction between pectin and the different hydrocolloids of agave leaves. These hydrocolloids might increase the use of Agave americana and be an alternative gel ingredient for the food industry.